Determinación de los impactos ambientales por la apertura y lastrado del camino vecinal en la comunidad Cinco De Agosto – Río Conejo, en la parroquia Jambelí, cantón Lago Agrio, provincia de Sucumbíos. - Luzuriaga Rodríguez, Sonia Liliana (2016)
The investigation was realized in the Province of you Sucumbios, Canton Lago Agrio, Community on the fifth of August where an acces router will be constructed towards the community and in whose constructive phase the generation of impacts has identified like main problema associate environmental. The method of investigation of field used in the determination of the basicline consisted of the securing of samples representative of soil, water and the monitoring of the noise; while for the analysis of the Biotic component there was applied a Rapid Ecological Evaluation (direct remarks); the analysis of the socioeconomic component realized based on interviews the local inhabitants. In the determination and Evaluation of the Environmental impacts there was used the counterfoil of Leopold, of whose analysis the Plan of Environmental handling developed. The results obtained in the physical component, one determined that the components it waters down, soil air meet inside the permissible limits as the comparison the TULSMA; as for the flora and fauna it is considered to be representative of the sector, also the identified species are not catalogued like vulnerable or in extinction danger; in the socioeconomic aspect the surveys and interviews realized to the inhabitants reflect a high percentage of acceptance to the construction of the route. The totality of the certain impacts they were two hundred twenty-nine, of these the negative impacts are two hundred and one and positives, finally one proposed a Plan of Managing constituted of eight programs directed to anticipating, mitigating and compensating the environmental impacts. Key words. Line bases, environmental impacts, Plan of managing, abiótic, physical component.